Media Consumption and Fear of Crime: Evidence of the Need for an Intersectional Approach - Rosenberger, Jared S. (Victims & offenders, 2023)
Race/ethnicity, gender, and exposure to various types of media have been identified as important predictors of fear of crime. However, previous research largely fails to take a truly intersectional approach when testing this relationship. Utilizing a unique data source that oversamples for minority respondents and includes measures for social media, Internet, and traditional media consumption the current study attempts to fill this gap. Our research finds evidence that the link between media consumption and fear of crime varies significantly across intersectional subsamples of race/ethnicity and gender. This identifies a need for future intersectional research on fear of crime.